TEACHERS' PERCEPTION ON CLASSROOM MANAGEMENT, ASSESSMENT, AND TEACHING STRATEGY IN ENGLISH TEACHING BEFORE AND AFTER LESSON STUDY IMPEMENTATION (A Mixed-Method Study at Senior High Schools in Bandung) - Lukman Arif Rachman, - (2019)
This research investigated the English teachers' perception on classroom management, assessment, and teaching strategy before and after the implementation of the lesson study. The mix method was used in this research due to the data were collected and analyzed both in quantitative and qualitative in order to get deep teachers' perception before and after the lesson study implementation. This research used questionnaire, interview and observation rubric for collecting the data. The questionnaires were distributed to sixteen English teachers from three different high schools organized under the same foundation. The teachers were involved in the implementation of the lesson study and three teachers selected as the model teacher were further interviewed to validate the questionnaire results. The questionnaire and interview were conducted before and after the implementation of the lesson study. Observation rubrics were also used to observe the three cycles of the lesson study implementation. The findings revealed that the teachers' perception on classroom management, assessment, and teaching strategy had changed due to the collaboration and sharing process among the teachers in the lesson study implementation. In addition, the implementation of the lesson study had improved the quality of teaching and learning in the classroom from the first cycle to the third cycle. This research was expected to be references for teachers and other researcher on the implementation of the lesson study in English teaching at high schools. Moreover, this research was essential to investigate the effect of the implementation of the lesson study on English teaching. Penelitian ini berjudul "Persepsi Guru dalam Manajemen Kelas, Penilaian, dan Strategi Pengajaran dalam Pengajaran Bahasa Inggris Sebelum dan Sesudah Pelaksanaan lesson study". Penelitian ini juga mengamati bagaimana lesson study diterapkan dalam pengajaran Bahasa Inggris. Penelitian ini menggunakan tiga instrumen dalam mengumpulkan data berupa angket, wawancara dan rubrik observasi. Angket diberikan kepada enam belas guru Bahasa Inggris dari tiga sekolah menengah atas swasta di bawah yayasan pendidikan yang sama untuk mendapatkan persepsi guru dalam manajemen kelas, penilaian, dan strategi pengajaran dalam pengajaran Bahasa Inggris. Keenam belas guru Bahasa Inggris adalah guru yang terlibat dalam pelaksanaan lesson study. Selain itu, wawancara dilakukan kepada tiga guru yang telah menjadi guru model dalam implementasi lesson study. Wawancara bertujuan untuk mendukung data yang telah didapat dari angket. Ketiga guru bahasa Inggris tersebut adalah guru yang telah menjadi guru model dalam pelaksanaan lesson study. Angket dan wawancara diberikan sebelum dan sesudah pelaksanaan lesson study untuk mengetahui persepsi guru akan manajemen kelas, penilaian, dan strategi pengajaran dalam pengajaran Bahasa Inggris sebelum dan sesudah pelaksanaan lesson study. Rubrik observasi juga digunakan untuk mengamati pelaksanaan lesson study selama tiga siklus dalam pengajaran Bahasa Inggris. Hasil penelitian menunjukkan bahwa pelaksanaan lesson study dapat merubah persepsi guru dalam manajemen kelas, penilaian, dan strategi pengajaran yang mana meliputi bahan ajar, media pengajaran, dan strategi pengajaran dalam pengajaran Bahasa Inggris sebagai dampak dari kolaborasi dan kesempatan untuk berbagi di antara para guru selama pelaksanaan lesson study. Selain itu, bila dibandingkan dari siklus pertama hingga ke siklus ketiga, terdapat peningkatan kualiats pebelajaran di kelas. Penelitian ini diharapkan dapat memberikan kontribusi sebagai sumber profesional untuk guru dan peneliti lain tentang penerapan lesson study dalam pengajaran Bahasa Inggris di tingkat sekolah menengah atas. Selain itu, penelitian ini dapat menjadi referensi untuk mengungkapkan dampak pelaksanaan lesson study dalam pengajaran Bahasa Inggris.